Pengaruh Pelayanan Koperasi Setjen DPR-RI Terhadap Kesejahteraan Karyawan Pegawai Negeri Sipil DPR-RI di Wisma Griya Sabha DPR-RI. - Martina Safitri; Amelia Amelia (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2018)
In the case of serving a person, the service has standardization to be run by employees in order to create a good influence, and the benchmark used in terms of service is as a reference quality of service to be provided or promised to customers or members. In accordance with the benchmark then the service must be created optimally and prime, which is the excellent service that is good service and even very good done by employees to customers or members. The purpose of this study is to determine the effect of cooperative service of the General Secretariat of the House of Representatives on the welfare of the employees of the DPR RI civil servants in Wisma Griya Sabha DPR RI. This research method using descriptive method. This research was conducted for 3 (Three) months, ie from May to July 2011. The research was conducted at Wisma Griya Sabha DPR-RI with address Jl. Raya Peak kp. Kebon Cau Kopo, Cisarua Sub-district, Bogor Regency. The population of this research is Employee of Civil Servant of DPR-RI at Wisma Griya Sabha DPR-RI Bogor Regency, which amounts to 30 people.             The result of the research shows that the service of the general staff of the secretariat of DPR-RI can be quite good with the percentage of 43.3%. Welfare of the secretariat general staff of DPR-RI get percentage of 4.60% which means bigger than the service level of the General Staff Cooperative of DPR-RI Secretariat Based on regression and correlation analysis it can be seen that there is a positive relationship between Service Cooperative Employees Secretariat General DPRI -RI Against Employees' Welfare Employees.